PENGAWASAN PEMBIAYAAN PENDIDIKAN DI MADRASAH (STUDI KASUS DI MTS WIHDATUL FIKRI KABUPATEN BANDUNG) - Ace Somantri; Mochamad Fadlani Salam (Universitas Muhammadiyah Prof Dr Hamka, 2021)
Funding and accountability have always been a major problem in financial management of education in Indonesia. The purpose of this research is to know the financial management of education at MTs. Wihdatul Fikri on the aspect of funding sources and accountability of Madrasah. This research was a qualitative research using a case study method. The data collection techniques used in this study were documentation and in-depth interview. The results showed that 1) MTs. Wihdatul Fikri relied on tuition fees on BOS from government (the government fund from 2014 to 2016 was Rp. 207,850,000); 2) from 2014 to 2016 other sources of funds received by MTs. Wihdatul Fikri only came from IP (Indonesian Power) and individuals which was lower than those from government (Rp. 69,200,000); 3) the accountability of MTs. Wihdatul Fikri was low because there was no transparency in the report of madrasah accountability, either related to BOS funds or other funds from IP.